One-pot sequential synthesis of isocyanates and urea derivatives via a microwave-assisted Staudinger–aza-Wittig reaction - Carnaroglio, Diego; Martina, Katia; Palmisano, Giovanni; Penoni, Andrea; Domini, Claudia; Cravotto, Giancarlo (Beilstein Journal of Organic Chemistry, 2013)
A fast and efficient protocol for the synthesis of N,N'-disubstituted urea derivatives from alkyl halides and primary or secondary amines has been developed. The synthetic pathway combines nucleophilic substitutions and a Staudinger–aza-Wittig reaction in the presence of polymer-bound diphenylphosphine under 14 bar of CO2 pressure and has been performed in a one-pot two-step process. The protocol has been optimized under microwave irradiation and the scale-up experiment has been conducted under conventional conditions in a Parr reactor. The final compounds were isolated after simple filtration in almost quantitative overall yields which makes this procedure facile and rapid to execute.
Keywords: isocyanates; microwave-assisted reaction; one-pot reaction; tandem Staudinger–aza-Wittig reaction; urea derivatives